Average Daily Gain and Energy and Nitrogen Requirements of 4-Month-Old Female Yak Calves - Bai, Binqiang; Degen, A. Allan; Han, Xiaodong; Hao, Lizhuang; Huang, Yayu; Niu, Jianzhang; Liu, Shujie (Frontiers in Veterinary Science, 2022)
There is little information available on milk intake and energy and nitrogen requirements of growing yak calves. This study aimed to fill this important gap, as this information could be beneficial in designing a system to wean yak calves earlier than in natural time. We determined the average daily gain and energy and nitrogen balances and requirements of 4-month-old female yak calves (48.8 ± 2.45 kg, n = 8). The calves were allowed to suck once a day and were fed an ad libitum concentrate: hay diet at a ratio of 60:40. Milk intake averaged 540 ± 26 g/d, yielding 2.28 ± 0.112 MJ/d, which was 13% of the gross energy intake (GEI). The digestible energy intake (DEI):GEI ratio was 0.681, metabolizable energy intake (MEI):DEI was 0.913, and MEI:GEI was 0.621. The average daily gain of the calves was 433 ± 153.1 g/d, which consisted of 78.0 ± 8.99 g protein, 52.7 ± 23.74 g fat, and 302.3 ± 95.1 g water, that is, 18.0% protein, 13.0% fat and 69.8% water. There were 130.7 g of body solids and 9.06 MJ of energy in every kg of body mass gain. Of the MEI, 25.17 kJ were required for 1 g of body mass, 83.40 kJ for 1 g of body solids, and 2.62 kJ for 1 kJ of retained energy (RE), and RE was 36.6% of MEI. The maintenance energy requirement was 5.35 MJ/d, the efficiency of utilization of energy for growth (kg) was 0.72, and the heat increment of feeding for growth was 0.28 (1.55 MJ/d). Digestible nitrogen (N) was 0.685 while retained N (RN) was 0.489 of N intake. The N requirement for maintenance was 11.73 g/d or 0.61 g N/kg0.75 per day, while the biological value (BV) of N was 91.1%. The energy and N requirements for yak calves were relatively low, which could be explained, at least in part, by the high efficiency of utilization of energy and high BV of N when compared to other livestock. These findings could be beneficial in designing early weaning systems for the many Himalayan households depending on yak production for their livelihoods.